The Flavian Officina Lapidaria Tarraconense: colour and texture in the service of Rome - Gorostidi Pi, Diana; Ruiz Rodríguez, Julio César (Studia Europaea Gnesnensia, 2017)
We present a reflection on the workshops charged with shaping the public image of Flavian Tarraco through its epigraphic monuments. For this purpose, we undertooka detailed analysis of the materials and media used to decorate the areas of representation of the Concilium Provinciae, established at the beginning of Vespasian’s reign, contrasting them with the epigraphic production of the preceding periods. The study is compared to other archaeological relics from the same area.